2016
DOI: 10.1016/j.athoracsur.2015.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Mini Bypass and Proinflammatory Leukocyte Activation: A Randomized Controlled Trial

Abstract: Both p38-MAPK activation and ROS were attenuated with the use of mCPB compared with cCPB, providing a potential mechanism for reduced inflammation in association with CPB miniaturization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In addition, monocytes could activate T and B lymphocytes and further produce cytokines such as IL-12 and TNF-α to stimulate the immune response [ 17 ]. However, either overstimulation or immunosuppression of monocytes caused by surgical procedure and/or other external factors could disrupt the immune system [ 18 , 19 ]. Previous studies have shown an elevated preoperative monocyte count to be a poor prognostic factor in esophageal squamous cell carcinoma, mantle cell lymphoma, follicular lymphoma, and classical Hodgkin lymphoma, respectively [ 6 , 7 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, monocytes could activate T and B lymphocytes and further produce cytokines such as IL-12 and TNF-α to stimulate the immune response [ 17 ]. However, either overstimulation or immunosuppression of monocytes caused by surgical procedure and/or other external factors could disrupt the immune system [ 18 , 19 ]. Previous studies have shown an elevated preoperative monocyte count to be a poor prognostic factor in esophageal squamous cell carcinoma, mantle cell lymphoma, follicular lymphoma, and classical Hodgkin lymphoma, respectively [ 6 , 7 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported also by the study by Halonen et al [19] in which the incidence of postoperative AF was significantly lower in patients treated with intravenous metoprolol as compared to metoprolol by mouth. Evolution of the cardiopulmonary bypass has emerged new techniques such as MECC to reduce the inflammatory response follow cardiac surgery [21][22][23]. Reducing the surface area of the circuit and removing the blood-air interface potentially offers several benefits compared to CECC including reduced hemodilution, postbypass coagulopathy, and inflammatory response [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…New techniques, such as miniaturized ECC (MECC), have been developed to reduce blood-air and blood-artificial material contact and, thus, inflammatory response compared to conventional ECC (CECC) [21][22][23]. In addition, an increasing number of CABG procedures are performed without any ECC (OPCAB) aiming to less surgical trauma and even less inflammatory reaction than with CECC or MECC [24,25].…”
mentioning
confidence: 99%
“…However, either overstimulation or immunosuppression of monocytes caused by surgical procedure and/or other external factors could disrupt the immune system (18,19). Previous studies have found an elevated preoperative monocyte count tumor-associated macrophages (TAMs), which further promote those invading leukocytes to bring out potentials of angiogenesis, motility, and invasion (25,26).…”
Section: Discussionmentioning
confidence: 99%